Circulating microRNAs in suspected stable coronary artery disease: A coronary computed tomography angiography study. (19th June 2019) - de Gonzalo‐Calvo, David; Vilades, David; Martínez‐Camblor, Pablo; Vea, Àngela; Nasarre, Laura; Sanchez Vega, Jesus; Leta, Rubén; Carreras, Francesc; Llorente‐Cortés, Vicenta
Abstract: Objectives: To explore the diagnostic performance of circulating microRNAs (miRNAs) as biomarkers in patients with suspected stable coronary artery disease (CAD). Methods: Plasma samples were collected from 237 consecutive patients referred for coronary computed tomography angiography (CCTA). Presence, extension and severity of coronary stenosis were evaluated using the indexes: presence of diameter stenosis ≥ 50%, segment involvement score (SIS), segment stenosis score (SSS) and 3‐vessel plaque score. A panel of 10 miRNAs previously associated with CAD was analysed using RT‐qPCR. Multivariate analyses were used to analyse the associations between biomarkers and indexes. Discrimination was evaluated using the area under the ROC curve (AUC). Decision trees were generated using chi‐squared Automatic Interaction Detector (CHAID) prediction models. Results: After comprehensive adjustment including cardiovascular risk factors, medication use, confounding factors and protein‐based biomarkers (hs‐TnT and hs‐CRP), several circulating miRNAs were inversely associated with coronary atherosclerosis extension (SIS and 3‐vessel plaque score) and severity (SSS). In the whole population, circulating miRNAs showed a poor discrimination value for all indexes (AUC = 0.539–0.644) and did not increase the discrimination capacity of a clinical model of coronary stenosis presence, extension and severity based on conventional cardiovascular risk factors. Conversely, the inclusion of circulating miRNAs in decision trees produces models that improve the classification of cases and controls in specific patient subgroups. Conclusions: This study identifies a group of circulating miRNAs that failed to improve the discrimination capacity of cardiovascular risk factors but that has the potential to define specific subpopulations of patients with suspected stable CAD. Abstract :